Wykonaj działanie.
a)3a(a-2)=
b)-2a(6a+4)=
c)(a+7)(2a-4)=
d)-(a-1)(½a-2)=
e)(a+5)²-10a=
f)(a-4)²-16=
Potrzebuję na teraz? daje naj?​



Odpowiedź :

Od a) do c)

[tex]3a(a-2)=3a^2-6a\\\\-2a(6a+4)=-12a^2-8a\\\\(a+7)(2a-4)=2a^2-4a+14a-28=2a^2+10a-28[/tex]

Od d) do f)

[tex]-(a-1)(\frac{1}{2}a-2)=-(\frac{1}{2}a^2-2a-\frac{1}{2}a+2)=-(\frac{1}{2}a^2-2\frac{1}{2}a+2)=-\frac{1}{2}a^2+2\frac{1}{2}a-2\\\\(a+5)^2-10a=a^2+2\cdot a\cdot5+5^2-10a=a^2+10a+25-10a=a^2+25\\\\(a-4)^2-16=a^2-2\cdot a\cdot4+4^2-16=a^2-8a+16-16=a^2-8a[/tex]

Wykorzystałam dwa wzory skróconego mnożenia

[tex](a+b)^2=a^2+2ab+b^2\\\\(a-b)^2=a^2-2ab+b^2[/tex]